Cooperative caching for grid-enabled OLAP. (18th December 2008) - Dehne, F.; Lawrence, M.; Rau-Chaplin, A.
In this paper, we propose a grid-based On-Line Analytical Processing (OLAP) application which distributes query computation across an enterprise grid. Our application follows a two-tiered process for answering queries based on sharing Cached OLAP data between the users at the local grid site and using grid scheduling approaches to execute the remaining parts of a query amongst a distributed set of OLAP Servers. A new technique for extraction and aggregation of shared Cached OLAP data is proposed, along with an efficient, aggregate-aware Cache controller. An experimental evaluation of the proposed query processing and cooperative Caching methods shows a significant reduction in query times compared to previously proposed methods.